Protein Phosphatases and Alzheimer’s Disease - Braithwaite, Steven P. (2012)
Alzheimer’s Disease (AD) is characterized by progressive loss of cognitive function, linked to marked neuronal loss. Pathological hallmarks of the disease are the accumulation of the amyloid-β (Aβ) peptide in the form of amyloid plaques and the intracellular formation of neurofibrillary tangles (NFTs). Accumulating evidence supports a key role for protein phosphorylation in both the normal and pathological actions of Aβ as well as the formation of NFTs. NFTs contain hyperphosphorylated forms of the microtubule-binding protein tau, and phosphorylation of tau by several different kinases leads to its aggregation. The protein kinases involved in the generation and/or actions of tau or Aβ are viable drug targets to prevent or alleviate AD pathology. However, it has also been recognized that the protein phosphatases that reverse the actions of these protein kinases are equally important. Here, we review recent advances in our understanding of serine/threonine and tyrosine protein phosphatases in the pathology of AD.